The Teachers' Perception on Quality Management of Classroom in Pandemic Era vs. Post-pandemic Era - Ratih, Elisa; Sari, Ardiana (KnE Social Sciences, 2023)
This study explores the teachers’ perception on classroom management and the quality of the class, both in online and offline class. More specifically, it explores how the teachers manage their class in pandemic and post-pandemic era. Some questions in the form of questionnaire are employed in this study to examine the participants’ experiences in teaching English as a foreign language. The findings of this study indicate that offline class helps the teacher to manage and control the class well, compared to an online class Moreover, the students also have great enthusiasm in participating in teaching and learning activities. The study suggests that English teachers are required to apply some teaching strategies to manage and control the class, because it can impact the quality of the students to have a better performance in learning English. Keywords: English learning, offline class, online class, quality management